Thermosolvatochromism of 7H-indolo[1, 2-a]quinolinium dyes in pure solvents. (February 2021) - Sawicka, Marta J.; Wróblewska, Elwira K.; Lubkowski, Krzysztof; Sośnicki, Jacek G.
Abstract: Thermosolvatochromism of two dyes generated from hydroxyphenyl and hydroxynaphthyl derivatives of 7H-indolo[1, 2-a]quinolinium salts was studied in 14 pure solvents with polarities ranging from 155.3 to 249.5 kJ mol −1 according to E T (30) polarity scale. The measurements were carried out at temperatures ranging from −5 °C to 80 °C. The UV–Vis spectra of both compounds were found to be sensitive to temperature changes. In polar solvents, a decrease in temperature caused a hypsochromic shift in the UV–Vis spectrum of the studied dyes. In less polar solvents, a hypsochromic shift in the UV–Vis spectra of hydroxynaphthyl derivative with decreasing temperature was still observed, but in the spectrum of hydroxyphenyl derivative, a bathochromic shift was recorded. The results were compared with the spectral properties of Reichardt's dye. The influence of temperature on the absorption band position of hydroxynaphthyl derivative in many solvents was even greater than that of Reichardt's dye. The strength of solute-solvent interaction, as well as solvatochromic sensitivity and the type of solvatochromism (positive or negative), which the studied dyes exhibited, were taken into account in order to explain the obtained results. The VBHB model appeared to be very useful for interpretation of thermosolvatochromic properties of the studied dyes. Graphical abstract: Image 1 Highlights: 7H-indolo[1, 2-a]quinolinium derivatives show thermosolvatochromism. Hydroxynaphthyl derivative is more sensitive to temperature than Reichardt's dye. Temperature dependent solvent polarity influences the dye ground state structure. Weak solute-solvent interactions are responsible for greater temperature effect. ET (30) parameters are determined at 7 different temperatures for 14 solvents.